Market discipline: A review of the Mexican deposit market - Edgar Demetrio Tovar-García (Latin American Economic Review, 2014)
This paper studies the mechanisms of market discipline in the Mexican deposit market. It tests the hypothesis that low-quality banks pay higher interest rates on deposits, receive fewer deposits, and shift their deposit agreements from long to short term. This hypothesis was assessed with positive evidence in Mexico during the period 1991 - 1996, but was not checked again. This research uses a dynamic panel model and a sample of 37 banks from December 2008 to September 2012 to re-evaluate the market discipline hypothesis. The findings suggest a weak presence of discipline induced by depositors. Principally, market discipline is absent within market sectors.
Keywords: E59; G21; G39; 330; Market discipline; Deposit market; Bank risk; Mexico